Advancing SDG 4 through Effective Governance: A POAC-Based Educational Management Model for Early Childhood Literacy - Ida Farida; Rusijono Rusijono; Karwanto Karwanto (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The aim of the research was to develop and evaluate a POAC-Based Educational Management Model for literacy development in early childhood education and to assess its effectiveness and feasibility. Method: The study employed a Research and Development (R&D) approach using the ADDIE framework, integrating quantitative and qualitative methods. Data were collected through observations, interviews, questionnaires, documentation, reading journals, and expert validation, and analyzed using descriptive statistics and thematic analysis. Results: The proposed model achieved a 91.9% validity score and demonstrated high implementation effectiveness, with 93.1% in RA Ma'arif and 87.5% in TK Melati. The findings show that systematic planning, effective stakeholder coordination, structured implementation, and continuous monitoring significantly enhanced literacy development and fostered a sustainable literacy culture. These outcomes indicate that management-driven literacy programs can improve educational quality by ensuring consistent and collaborative literacy practices, supporting the achievement of SDG 4, particularly in promoting inclusive and equitable quality learning opportunities. Novelty: This study introduces a POAC-Based Educational Management Model that conceptualizes literacy development as a management-driven process rather than solely an instructional activity. The model provides a practical and sustainable framework for strengthening literacy culture in early childhood education institutions.This management-oriented approach contributes to the literature by offering an innovative strategy for advancing SDG 4, particularly through improving the quality, effectiveness, and sustainability of literacy education in early childhood settings.